Intrahepatic cholestasis of pregnancy – a candidate gene study. (7th June 2011) - Dixon, P H; Wadsworth, C; Chambers, J; Donnelly, J; Cooley, S; Jarvis, S; Kubitz, R; Lammert, F; Marschall, H-U; Glantz, A; Khan, S; Whittaker, J; et al.
Abstract : Intrahepatic cholestasis of pregnancy (ICP) has a complex aetiology. Genes mutated in progressive familial intrahepatic cholestasis (PFIC) have been implicated in disease pathogenesis. Heterozygous mutations of these canalicular transporters occur in a subset of ICP cases. Genetic variation around the bile acid sensor FXR ( NR1H4 ) has also been described, and a susceptibility allele (444A, ABCB11 ) identified. We expanded genetic analysis of ICP by investigating of common variation around six loci with biological plausibility for a role in ICP: ABCB4, ABCB11, ABCC2, ATP8B1, NR1H4, FGF19. 563 ICP patients of white western European origin together with 642 controls from the Rotunda Thrombophilia study were analysed. 83 markers were selected from the HapMap dataset (Tagger, Haploview 4.1, b22) capturing the majority of common genetic variation around the loci. Genotyping was performed by a proprietary allelic discrimination assay. Following QC including conformation of Hardy-Weinberg equilibrium (HWE), SNP data and haplotyes were analysed (trend testing, haplostats). 78 markers passed quality control and HWE tests. Single SNP analysis identified six SNPs in ABCB11 and six in ABCB4 that showed significant evidence of association. The minimum Bonferroni corrected p-value for ABCB11 was 3.7×10–4 ( rs3815676 ) and for ABCB4 3.4×10–7 ( rs2109505 ). Haplotype analysis identified significant differences in frequencies between cases and controls for ABCB4 (p=9.6×10–6) and ABCB11 (p=0.0036). Our analysis of a large cohort of ICP cases has identified a key role for common variation around the ABCB4 and ABCB11 loci, expanding on the genetic factors known to play a role in susceptibility to this disease.